The - Stevens, Luke
The Truth About HTML5 is for web designers, web developers, and front-end coders who want to get up to speed with HTML5. The book isn't afraid to point out what everyone gets wrong about HTML5's new markup, so you don't make the same mistakes. It will show you what rocks in HTML5 today and what the future holds